Modelling of Magnetorheological Fluids with Combined Lattice Boltzmann and Discrete Element Approach (Communications in Computational Physics, 2010)
A combined lattice Boltzmann and discrete element approach is proposedfor numerical modelling of magnetorheological fluids. In its formulation, the particledynamics is simulated by the discrete element method, while the fluid field is resolvedwith the lattice Boltzmann method. The coupling between the fluid and the particlesare realized through the hydrodynamic interactions. Procedures for computing magnetic,contact and hydrodynamic forces are discussed in detail. The applicability ofthe proposed solution procedure is illustrated via a two-stage simulation of a MR fluidproblem with four different particle volume fractions. At the first stage, simulationsare performed for the particle chain formation upon application of an external magneticfield; and at the second stage, the rheological properties of the MR fluid underdifferent shear loading conditions are investigated with the particle chains establishedat the first stage as the initial configuration.